Hoary basil seed mucilage as fat replacer and its effect on quality characteristics of chicken meat model - Saengphol, Ekkarach; Pirak, Tantawan (Agriculture and Natural Resources, 2018)
The effect of chicken breast meat source and main ingredients (salt, pork back fat (BF) and hoary basil mucilage (HBM)) on sensory perception and quality characteristic of meat products was investigated. Three different meat sources were selected and assigned as Brand A, B and C. Brand C had highest protein content (26.38%) and extracted salt soluble protein content (7.54%), which indicated the nutritional and quality of meat. This sample was used for investigating the effect of salt (1% and 2%) and BF to HBM ratio (100:0 to 0:100) on meat product model properties. The significant effect of these factors was detected (p < 0.05). The model with 2% salt without HBM possessed the gels with superior texture and sensory properties; however, HBM was able to substitute as BF replacer at 80% (2% salt) without any change of sensory perception from 100% BF model.